Supporting Student Veteran Success at Madison's Postsecondary Institutions - Shumway, Michael; Koepsel, Tami; Bechtol, John (My University, 2009)
The recent adoption of the Post-9/11 GI Bill has made postsecondary education accessible to many veterans returning from Iraq and Afghanistan. As a result, the program will bring thousands of veteran students to campuses throughout the Midwest and the nation. This potential influx of students has prompted colleges and universities to rethink current policies and procedures in order to help better serve the unique needs of veterans. In this brown bag forum, a panel of representatives from three Madison campuses?each with differing missions and services?will describe their institutions? responses to the needs of student veterans. The event will engage policymakers, academic professionals, and veterans in a discussion of the present and future of student veterans? services in postsecondary education, paying close attention to several issues that many veterans identify as particularly pressing, such as the Yellow Ribbon Program and transfer credits for training received while in the military.
Keywords: Access, Persistence, and Success; Student Affairs